Punch-through and junction breakdown characteristics for uniaxial strained nano-node metal-oxide-semiconductor field-effect transistors on (100) wafers. (1st January 2014) - Wang, Mu-Chun; Huang, Heng-Sheng; Peng, Min-Ru; Wang, Shea-Jue; Chen, Tsao-Yeh; Liao, Wen-Shiang; Yang, Hsin-Chia; Liu, Chuan-Hsi
In the nano-regime MOSFET devices, the punch-through effect is more distinct, retarding the reliability tolerance, such as electro-static discharge or latch-up applications. Through the measurement in various device lengths under contact-etch-stop-layer strain process or without strain effect for 45 nm complementary MOS process, the difference of punch-through effect and junction breakdown integrity were able to be classified and exhibited in design applications. After tested data analysis, the junction breakdown issue in PMOSFET was usually greater than that in NMOSFET due to the doping concentrations and the doping species. Generally, the junction breakdown value is independent of channel length variation except the existence of some damage close to the gate/source or gate/drain fringe. In addition, the punch-through voltage for PMOSFET as source/drain current IDS = 1 μA is also larger than that observed for NMOSFET.